METHODS AND ANALYSIS OF THE HSX TRANSMISSION LINE WITH SMOOTH-WALL AND PERTURBED-WALL LAUNCHERS - Buscarino, Eric (My University, 2013)
Gaussian beams are electromagnetic waves with Gaussian distribution amplitudes in the transverse directions and are important for electron cyclotron heating (ECRH) in many plasma fusion experiments. Systems that have the ability to transform the non- Gaussian output of some gyrotrons are of particular interest and it is important to understand the limits of the methods used in designing and simulating these systems. The computational propagation of Gaussian beams is important in the design and modeling of complex and high-power systems. Therefore it is important to understand the limits of where current approximate analytical solutions and computational methods differ. The first objective of this thesis is to analyze two computational methods of propagation, the Fourier Transform method and the Finite-Difference Time-Domain method, and compare the results to the paraxial approximation solution for Gaussian beams. Specifically, these methods are tested for initial beam waist radii in the region of a wavelength or less than a wavelength. It was found that there was good agreement between each method and that it would be advisable to use FFT for narrow beam freespace propagation and FDTD for domains consisting of scatterers. A perturbed-wall launcher designed by Ungku Fazri Ungku Farid was implemented in the HSX microwave transmission system and simulated using Surf3d. The original smooth-wall Vlasov launcher HSX microwave transmission system was also simulated and found to have 63% of the input power propagated to the dual-mode waveguide, while the perturbed-wall launcher only propagated less than 10%. The original launcher also propagated a beam to the dual-mode waveguide containing significantly more Gaussian content than the perturbed-wall launcher beam. This significant performance decrease is due to the HSX microwave transmission system being designed using geometrical optics for shaping the output beam of the smooth-wall Vlasov launcher and, if redesigned for the perturbed-wall launcher, the system could realize increased propagated power. For the perturbed-wall system there should be less power loss and less spillover loss in the system due to a better output beam from the launcher.
Keywords: electron cyclotron heating; electromagnetic waves; Gaussian beams